Practical Application of Copepod Oithona sp. Meal Supplementation in Feed as a Promoter of Survival and Growth in Vannamei Shrimp (Litopenaeus vannamei) - Heriansah Heriansah; Fathuddin; Nursyahran; Arnold Kabangnga; Buana Basir; Mesalina Tri Hidayani; Nursidi (Department of Aquaculture, 2026)
The nutritional potential of copepods as live feed for larvae warrants further exploration, particularly for juvenile and adult shrimp. However, their small size presents a challenge, as larger shrimp may struggle to capture such small prey. A nutrient-based formulation approach was adopted by supplementing Oithona sp. copepod meal into vannamei shrimp (Litopenaeus vannamei) feed, and its effects on survival and growth were evaluated. A 35-day experiment was conducted in aquariums (20×20×30 cm) with an 8-liter water volume. The experimental feed was prepared by coating it with copepod meal. Four supplementation levels, each with three replicates, were tested: 0, 1, 2, and 3 g per 100 g of feed. Vannamei shrimp with an initial weight of 2.15±0.03 g and a stocking density of 16 individuals per aquarium were fed three times a day to satiation. Although the differences were not statistically significant, the survival rate of shrimp fed with supplemented diets (all 100±0.00%) was higher than that of the non-supplemented group (97.9±3.6%). In terms of growth, Absolute Weight Gain (AWG) and Specific Growth Rate (SGR) were significantly higher in the 3 g (5.27±0.02 g and 3.53±0.01% day-1), 2 g (5.13±0.08 g and 3.51±0.06% day-1), and 1 g group (4.88±0.10 g and 3.36±0.07% day-1) compared to the non-supplemented group (2.97±0.13 g and 2.48±0.11% day-1). In conclusion, the supplementation of copepod meal effectively enhanced the survival and growth of vannamei shrimp. The 3 g dose is the best dose that promotes the highest growth and survival.